Analysis of Allocative Efficiency in Rice (Oryza sativa L.) Farming in the Batu Alam Industrial Area, Cirebon Regency - Sarifuddin, Ujang; Rosmawati, Misy; Mardhatillah, Farida; Wahana, Siti (Ann Publisher, 2024)
This research analyzes the efficiency of farming costs and the factors influencing rice farming costs. The research method used was descriptive quantitative with data collection techniques through surveys and interviews with 176 rice farmer respondents in the natural stone industrial area of Cirebon district. The analysis used is frontier cost analysis using frontier4.1 software using the Maximum Likelihood Estimation (MLE) approach. This research shows that the average cost efficiency or allocative level in the natural stone industrial area is 0.20. The factor that influences the inefficiency of rice farming in natural stone industrial areas is age. Factors directly influencing farming costs are land area, urea, labor, rice selling price, land rental price, and labor wages.